SPECIES COMPOSITION, STRUCTURE, AND MANAGEMENT IN GAYO COFFEE-BASED AGROFORESTRY SYSTEM: The Case of Mude Nosar Village, Central Aceh Regency - Hartoyo, Adisti Permatasari Putri; Hutagalung, Labana; Kulsum, Fifit; Sunkar, Arzyana; Herliyana, Elis Nina; Hidayati, Syafitri (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Gayo coffee has many benefits in terms of the environment, economy, and socio-cultural aspects, especially for the Gayo tribe. Recently, Gayo coffee has been the main commodity for the plant cultivation of the Gayo tribe, including the Mude Nosar as local farmers. One of the ways to cultivate Gayo coffee is through an agroforestry system. However, limited reports on the tree species composition and its management in Gayo coffee-based agroforestry needs to be explored. This study aims i) to identify the tree species composition and structure, as well as 2) to analyze the management of Gayo coffee-based agroforestry system in Mude Nosar Village. The study method used plot establishment for vegetation analysis, and interviewed the Gayo coffee farmers. The results showed that the number of tree species at all growth stages was 26 species. The highest Important Value Index (IVI) at the understory and sapling level in order was rumput kerbau (Paspalum conjugatum) and Gayo coffee (Coffea arabica), while at the seedling, pole, and tree levels were dominated by lamtoro (Leucaena leucocephala). The local farmers often use lamtoro as a shade tree for Gayo coffee in agroforestry system. The species diversity index (H') showed low values at all growth levels, except for understory plants with moderate values. The horizontal structure of the tree stand showed an inverted J curve, meaning that the regeneration rate is normal. The vertical structure of the tree stand belongs to strata C and D. The local farmers have applied good Gayo coffee management practices through an agroforestry system including land and seed preparation, planting, maintenance, and harvesting techniques. Coffee seeds and seedlings are from natural regeneration. Plant maintenance techniques are carried out by weeding, pruning, organic fertilization, and controlling pests and diseases. The harvest coffee season is generally twice a year. The management of Gayo coffee using an agroforestry system impacts the ecological, economic, and social aspects.